Modification of the Regulatory Impact Assessment on Indonesia's Economic Policies - Verico, Kiki (UI Scholars Hub, 2018)
This paper modifies the Regulatory Impact Assessment (RIA) method in Indonesia's trade, investment, and industrial incentive policies. First, it analyses the Indonesian Bilateral Trade Agreements of Indonesia - Japan Economic Partnership Agreement (IJEPA) and Indonesia - Pakistan Preferential Trade Agreement (IP-PTA) This paper found if the trading partner has GNI per capita higher than Indonesia's then the expected outcome was the increasing FDI inflows and if its GNI per capita lower therefore the most top foreseeable result was the rising net trade balance of Indonesia. Second, it analyses industrial sector incentive analysis and found that firms prefer supply-side than fiscal incentives.